2010
DOI: 10.1051/0004-6361/201014803
|View full text |Cite
|
Sign up to set email alerts
|

A fundamental plane for field star-forming galaxies

Abstract: Context. Star formation rate (SFR), metallicity, and stellar mass are among the most important parameters of star-forming (SF) galaxies characterizing their formation and evolution. They are known to be related to each other both at low and high redshift in the mass-metallicity, mass-SFR, and metallicity-SFR relations. Aims. We demonstrate the existence of a plane in a 3D parameter space defined by the axes SFR [log (SFR)(M yr −1 )], gas metallicity [12 + log (O/H)], and stellar mass [log (M star /M )] of SF g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
441
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(485 citation statements)
references
References 50 publications
30
441
13
1
Order By: Relevance
“…This picture is also in agreement with the observed fundamental metallicity relation (FMR; Lara-López et al 2010;Mannucci et al 2010;Stott et al 2013b) in which galaxies at a fixed stellar mass are found to be more metal poor with increasing SFR. In fact, as measurements of the FMR tend to use spectroscopy of the bright inner regions of the galaxy due to the limited size of spectroscopic slits and fibres (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…This picture is also in agreement with the observed fundamental metallicity relation (FMR; Lara-López et al 2010;Mannucci et al 2010;Stott et al 2013b) in which galaxies at a fixed stellar mass are found to be more metal poor with increasing SFR. In fact, as measurements of the FMR tend to use spectroscopy of the bright inner regions of the galaxy due to the limited size of spectroscopic slits and fibres (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The relationship presents a significant scatter that has been recently found to be associated with the present SFR in the galaxy Lara-López et al 2010;Yates et al 2012;Pérez-Montero et al 2013;Andrews and Martini 2013;Zahid et al 2013). Specifically, for galaxies with the same stellar mass, the metallicity decreases as the current SFR increases.…”
Section: The Stellar Mass-metallicity-sfr Relationshipmentioning
confidence: 64%
“…It was argued in some recent papers (e.g. Manucci et al 2010;Lara-López et al 2010;Hunt et al 2012;Andrews & Martini 2013) that star-forming galaxies with higher SFRs are systematically more metal-poor on the stellar massmetallicity diagrams. In particular, Manucci et al (2010) proposed a fundamental metallicity relation (FMR) between stellar mass, gas-phase metallicity and star formation rate.…”
Section: Stellar Mass -Metallicity Relationmentioning
confidence: 99%